PELATIHAN RANCANG BANGUN DAN PEMANFAATAN MESIN PEMARUT KELAPA PORTABLE DI DESA JOGOSATRU SIDOARJO - Yayu Sriwahyuni Hamzah; Utami Puji Lestari; Abdul Malik Perwira Negara; Andika Wachid Nur Aziz; Dimas Permana Putra (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The design and use of a portable coconut grater machine is very important in supporting the business productivity of traditional snack traders in the village of Jogosatru, Sidoarjo. The purpose of this PKM is to make a portable coconut grater machine that has a simple, inexpensive, easy-to-operate and easy-to-maintain system, so that it can be used to support the business productivity of traditional snack traders in particular and the people of Jogosatru Village in general. The method used in this service is Asset-Based Community Development (ABCD). The result of this service activity is that 100% of the community partners (traditional snack traders) are able to operate and maintain a portable coconut grater machine. And 100% of the community partners (Karang Taruna) are able to make and assemble portable coconut grater machines.